PENGARUH ECONOMIC VALUE ADDED, MARKET VALUE ADDED, RETURN ON ASSET DAN RETURN ON EQUITY TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR KONSTRUKSIDI BURSA EFEK INDONESIA PERIODE 2005â 2012 - Purnomo, Yuni (Jurnal Tepak Manajemen Bisnis, 2015)
This study aims to determine the financial performance in the construction services industry will be seen by the performance of the Economic Value Added, Market Value Added, Return On Assets and Return On Equity and its impact on company value so it can be a reference for investors and prospective investors to look at and assess the companies financial condition. Furthermore, it can obtain the most influential indicators between EVA, MVA, ROA and ROE to the Companys value.This study uses a quantitative study with nine samples are listed construction company listed on the Indonesia Stock Exchange. Data obtained through the online medium to collect the Yahoo Finance reports published by the Indonesia Stock Exchange and then analyzed with multiple regression effect on the level of 95% with the help of Statistic Program for Social Science (SPSS) version 17.The results showed that, all of nine companies have created a good value added for shareholders, although there are any companies that have lowered the value of his company. The results of this study indicate that the variable EVA, MVA, ROA and ROE are simultaneous and significant effect on the value of the Company. Partial test showed that MVA and ROA significant effect on the Companys value, while the EVA and ROE and no significant negative effect on the value of the Company. The results of the analysis of the standardized beta coefficients of each independent variable showed that MVA is the most dominant influence.Key words: Economic Value Added, Market Value Added, Return On Assets, Return On Equity and Corporate Value.